Reconstruction of Law Enforcement Against Narcotics Distribution Networks Through A Restorative Justice-Based Money Laundering Criminal Approach for Children Exploited as Couriers - Yudi Bintoro; Megawati Barthos (Jurnal Sosial Teknologi, 2026)
The involvement of children as couriers in narcotics distribution networks presents a systemic problem in Indonesian criminal justice, where law enforcement has disproportionately targeted field-level perpetrators while failing to dismantle the economic structures controlled by intellectual actors. This research aims to analyze the normative disharmony between Law Number 35 of 2009 concerning Narcotics, Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, and to reconstruct a law enforcement model that integrates asset confiscation with restorative justice for exploited children. This research employs a normative legal methodology with statutory, conceptual, and case approaches analyzed qualitatively. The findings reveal that existing regulations lack integration, resulting in the criminalization of child couriers without addressing the financial networks behind them. Money laundering instruments remain underutilized, and diversion mechanisms are often unavailable due to severe sentencing thresholds. The study proposes a reconstructed model that shifts the enforcement focus from "follow the suspect" to "follow the assets," positions children as victims of structural exploitation, and directs them toward restorative mechanisms. In conclusion, integrating asset confiscation against key actors with restorative diversion for children creates a fairer and more effective law enforcement system, ensuring that narcotics eradication targets network structures while safeguarding children's futures